A multi-dimensional review on performance enhancement opportunities of next generation wave energy converters (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Wave energy converters (WECs) are viewed as one of the latest promising renewable energy sources. However, their development has been challenged due to many reasons ranging from the conceptual design stage to final installation, leading to higher Levelized Cost of Energy (LCOE). In this background, this paper reviews seven key areas to identify gaps towards performance excellence of WECs.  Firstly, design of WECs is discussed emphasizing device configuration, site selection, power take-off, mooring and stability, structural integrity and survivability.  Secondly, key prototype and subsystem failures of WECs are considered based on several case studies. Thirdly, the study focuses on the use of numerical and experimental approaches for WEC design. Fourthly, the paper presents gaps in system dynamics such as hydrodynamic and structural interactions, WEC farms and overall operation and maintenance aspects. As the fifth area of interest, efficiency improvement strategies such as advanced control strategies, device design improvements and the use of Artificial Intelligence in system optimization are discussed. Next, some of the latest trends such as combining WEC and Floating Offshore Wind Turbines (FOWTs) are presented. Eventually, as the seventh subtopic, the challenges and strategies towards reduction of LCOE are discussed. With these aspects sufficiently addressed by stake holders, it is expected that the overall reliability and performance optimizations will assure a sustainable growth in the WEC industry making net zero targets achievable by many nations.